Exploring Common solutions - Finland's Chairmanship Program for the Arctic Council 2017-2019 - Finnish Chairmanship (Arctic Council Secretariat, 2017)
Finland wants to highlight two recent milestones, which have major relevance for the Arctic: The legally binding climate agreement, concluded in Paris in 2015; and UN's 2030 Agenda for Sustainable Development. Finland intends to prioritize Environmental Protection, Connectivity, Meteorological Cooperation, and Education during the upcoming Chairmanship period.